Equivalence Parameters and Evaluation - Gerzymisch-Arbogast, Heidrun (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractThe article deals with the role of equivalence (parameters) in evaluating translated texts. After briefly portraying the controversy over the equivalence concept, it is proposed that this concept be considered on two levels: a system level on which Equivalence criteria are established and a text level on which a set of text-specific criteria is selected for evaluation purposes and the ranking of these criteria (from the evaluators point of view) with respect to their relevance in translating a particular text is made explicit. On a systems level it is suggested that the semantic network-based text and translation parameters of coherence, thematic and/or isotopic patterns be included in the catalogue of potential evaluation criteria. On a text level, possible motivations for translation variances in these parameters are discussed.